THE IMPLEMENTATION OF INCLUSIVE EDUCATION MODEL ON SOCIO-EMOTIONAL DEVELOPMENT OF CHILDREN WITH SPECIAL NEEDS IN EARLY CHILDHOOD EDUCATION - Priatiningsih Selasi (Journal of Education Technology and Inovation, 2024)
Inclusive education not only aims to provide learning space for children with special needs, but also encourages collaboration and understanding between students with diverse backgrounds. The application of an inclusive model is expected to be able to overcome social, cultural, and academic barriers that often hinder children's participation in formal education. This study uses a quantitative approach with a quasi-experimental design (quasi-experiment) with a nonequivalent control group design, Data analysis was carried out using parametric statistical tests paired sample t-test and independent sample t-test with a significance level (?) of 0.05 to determine significant differences in social emotional development before and after the intervention, Epistemologically, this study makes a significant contribution to the theory of inclusive education by showing that the social emotional development of children with special needs is greatly influenced by the quality of the design of the learning environment, social interaction, and systemic responsiveness to the diversity of individual needs